P14.06 Phase II randomized trial of short course hypofractionated radiotherapy with or without temozolomide in elderly patients with Glioblastoma. (6th September 2019) - Madan, R; Thakur, S; Salunke, P; Ahuja, C; Khosla, D; Yadav, B S; Kapoor, R; Kumar, N
Abstract: BACKGROUND: Glioblastoma (GBM) is the most aggressive primary brain tumor. Although treatment advances and introduction of temozolomide has improved the outcome in young patients, it is still a concern in elderly patients. Elderly population is often excluded from the trials, thus established treatment guidelines are not available. Trials have shown that short course hypofractionated radiotherapy (HRT) is equally effective in terms of overall survival (OS) and progression free survival (PFS) as compared to standard RT in elderly population. While the benefit of adding Temozolomide (TMZ) to standard dose radiotherapy is well established, there is lack of evidence that addition of TMZ to HRT improves survival in elderly patients.We conducted this study to see if addition of temozolomide to HRT improves OS, PFS and quality of life (QOL) in elderly GBM patients. MATERIAL AND METHODS: The study was conducted over a period of 21 months from January 2017 to September 2018. Histologically proven 70 newly diagnosed Glioblastoma patients (age>60 years) were enrolled and randomized into two arms (Arm I- HRT alone, Arm II- HRT and TMZ) using computer generated randomization table (1:1 ratio). The radiotherapy dose in both arms was same and consisted of a dose of 25Gy in 5 daily fractions over 1 week. In addition, arm II patients received daily concurrent TMZ 75mg/m 2 1 hour prior to RT followed by adjuvant TMZ 175mg/m 2 from Day1-5 for 6 cycles (q 4weeks), started after a month of RT completion. Quality of life score and global health status was assessed in both arms at baseline, 1, 3, 6 and 9 months after the treatment using QOL questionnaire EORTC QLQ-C 30 and QLQ-BN20. Data entry was done in Microsoft Excel 2016 and analysis was done in SPSS version 18. Kaplan Meier survival analysis was done for OS and PFS. To see the trend of time related observations at different point of time repeated ANOVA was used. A p value of <0.05 was taken significant. RESULTS: The median OS in arm I and II was 121 (range 40–360 days) and 146 (range 40–450 days) days respectively (P=0.146). The median PFS in arm 1 and arm 2 were 77 (range 30–300 days) and 109.50 (range 30–300) days respectively (p-0.028). On further analysis, the prognostic factors were type of surgery (Median PFS 159 days in gross total excision and 129 days in subtotal excision or biopsy, p-0.03) and KPS (0.04). QOL score for symptom and functional domain was comparable in both arms. However score of nausea and vomiting was higher during concurrent chemoradiotherapy. A non significant improvement in QLQ BN 20 score was observed at 9 months in arm I. CONCLUSION: Addition of Temozolomide to HRT is a compelling option in elderly Glioblastoma patients as it significantly improves the PFS and a non significant improvement in OS without compromising quality of life.